Note on Bodacious Biostatistics - Mulatu, Lemma; C’Asia Griffin; Sujin Kim (IJRDO -JOURNAL OF MATHEMATICS, 2020)
Biostatistics is the branch of statistics that deals with data relating to living organisms. Biostatisticians help answer pressing research questions in medicine, biology and public health, such as whether a new drug works, what causes cancer and other diseases, and how long a person with a certain illness is likely to survive. Biostatistics is the connector between math andscience as it is a field that merges passion and skill with biomedical science and mathematics and statistics and central to all of science, because science needs that gathering of evidence and the evaluation of that evidence to make a judgment. Biostatisticians use their quantitative skills to team up with experts in other fields, from biologists and cancer specialists to surgeons and geneticists. Most importantly, biostatisticians are not just individuals who deal with numbers only. They play pivotal roles in designing studies to ensure enough data and the right kind of information are collected. Then they analyze, evaluate and interpret the results – accounting for variables, biases and missing data along the way